2020
DOI: 10.3390/microorganisms8122006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a kDNA-Based qPCR Assay for the Detection and Quantification of Old World Leishmania Species

Abstract: The parasite protozoan Leishmania, the causative agent of leishmaniasis, includes two subgenera of medical interest: Leishmania (Leishmania) and Leishmania (Viannia). Parasite species detection and characterization is crucial to choose treatment protocols and to monitor the disease evolution. Molecular approaches can speed up and simplify the diagnostic process. In particular, several molecular assays target the mitochondrial DNA minicircle network (kDNA) that characterizes the Leishmania genus. We previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“…have 35 to 36 chromosomes in their nuclear genomes [ 35 , 36 ], and it is characterized by both mini and maxi circles kinetoplast DNA structures [ 37 ]. Various chromosomal and kinetoplast DNA sequences have been evaluated as targets for diagnostic systems and the extra-chromosomal circles showed always the best sensitivity and represent currently the most employed target with worldwide diffusion [ 38 , 39 ]. The use of high-copy 18S and minicircle kDNA sequences as a target usually allows amplification at the genus or subgenus level, due to their conserved sequences or to the heterogeneity of minicircle classes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…have 35 to 36 chromosomes in their nuclear genomes [ 35 , 36 ], and it is characterized by both mini and maxi circles kinetoplast DNA structures [ 37 ]. Various chromosomal and kinetoplast DNA sequences have been evaluated as targets for diagnostic systems and the extra-chromosomal circles showed always the best sensitivity and represent currently the most employed target with worldwide diffusion [ 38 , 39 ]. The use of high-copy 18S and minicircle kDNA sequences as a target usually allows amplification at the genus or subgenus level, due to their conserved sequences or to the heterogeneity of minicircle classes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…as evident from Leishmania -specific kinetoplast DNA transcript level ( Fig. S4 A ) ( 39 ). The results suggested that host Cu uptake and utilization is downregulated during the early stages of infection.…”
Section: Resultsmentioning
confidence: 94%
“…However, the specificity is low, and false-positive results may occur (van Griensven and Diro, 2019;Scarpini et al, 2022). In recent years, some studies have found that qPCR analysis of mitochondrial DNA minicircle network (kDNA) based on the characteristics of Leishmania genus has high sensitivity and specificity, and can thus be useful for quantitative detection of pan-Leishmania (Ceccarelli et al, 2020;de Carvalho et al, 2022;Mota et al, 2022). However, this technique is expensive and has not been used for routine clinical testing.…”
Section: Discussionmentioning
confidence: 99%